The Effects of Product Development on Customer Satisfaction - Motoh, Evelyn Regina; Waluyowati, Nur Prima (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to examine the effect of product development on consumer satisfaction among Fresh Care Smash consumers, focusing on product quality, variety, convenience, style, and design as key product development indicators. Design/Methodology/Approach – This study employs a quantitative research approach. Data were collected through questionnaires distributed to 100 respondents selected using a purposive sampling technique. The research instruments were tested for validity and reliability, followed by classical assumption tests, including normality, heteroscedasticity, and linearity tests. Data analysis was conducted using the coefficient of determination and t-test with SPSS version 30.0.0. Findings – The results indicate that product development has a significant effect on consumer satisfaction. Furthermore, product development indicators, including product quality, variety, style, and design, have positive and significant effects on consumer satisfaction. These findings demonstrate that improving product attributes and adapting products to consumer expectations can increase satisfaction and support customer loyalty in competitive markets. Originality/Value: This research provides value by empirically examining various dimensions of product development such as quality, variety, style, and design in relation to customer satisfaction in the context of Fresh Care Smash, a focus that remains understudied. The findings offer original insights that can guide companies in designing more customer-oriented product strategies to strengthen loyalty and market competitiveness.